General psychology with emphasis on human growth and development through the lifespan - Abelos, Alex Valentin; Basaen, Cleofas Miranda ; Payawal, Jaime Eusebio (Baguio City, 2005)
The book hopes specifically to enhance the learner's understanding of human behavior to answer the basic question: Why does man behave the way he does? Each lesson relates to what one already and commonly knows about a particular topic (domain knowledge); what one comprehends based on his own intellect (metacognition); and what beliefs, insights, attitudes, and emotionality one possesses within the context of learning (affective components). The study of psychology is thus one of the most interesting and stimulating course in the tertiary level due to ites inherent personal relevance to each learner
Keywords: Psychology